Behavior Modification in Quality Control - Adam, Everett E. (Academy of Management Journal, 1975)
Combined attitude change and operant conditioning procedures to improve operative worker performance were investigated. Results indicate no attitude change, no quality change, quantity improvement, and cost reduction. Based on this study, it is concluded that operant conditioning procedures did not provide an alternative to Zero Defects type quality motivation programs.